Strengthening Educational Literacy Among Fishing Families in Mendahara Ilir Village, Tanjung Jabung Timur - Nurhanisyah, Nurhanisyah; Abidin, Zainal; Daud, Daud; Hidayat, Wildan Nur (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
This study explores the dynamics of educational literacy within fishing families in Desa Mendahara Ilir, Tanjung Jabung Timur, focusing on how family practices, parental roles, community culture, and school-based initiatives contribute to children’s literacy development. Using a qualitative descriptive approach, data were collected through in-depth interviews, direct observations, and document analysis, then examined using thematic analysis to identify patterns across household and community contexts. The findings reveal that fishing families hold strong educational aspirations but face structural barriers such as economic instability, limited parental literacy, and irregular work routines that constrain their ability to support children’s learning at home. Schools compensate for these limitations by providing additional instructional support, reading programs, and culturally relevant literacy activities, while the community contributes through storytelling traditions, peer-learning networks, and collaborative initiatives. The study concludes that effective literacy strengthening in fishing communities requires integrated, context-sensitive strategies that empower families and leverage institutional and communal support systems to ensure sustainable literacy development.